PENAMBAHAN VITAMIN C PADA IKAN LELE DUMBO (Clarias gariepinus) UNTUK MENINGKATKAN TANGGAP KEBAL TERHADAP VAKSIN Aeromonas hydrophilia - Alim Isnansetyo (Jurnal Perikanan Universitas Gadjah Mada, 1996)
Motile Aeromonas Septicimia is a dangerous disease on fresh water fish especially walking catfish and carp. Vaccination against the disease has been developed in Indonesia. However, there were high result variations of the vaccination. Immune response is influenced by level of vitamin C dietery. Objective of this experiment was to know effect of vitamin c levels on walking catfish’s specific immune respose. The levels of vitamin (0, 50, 500, and 1000 mg ascorbic acid (AA)/kg feed) were given to the fish. Immersion vaccination for 30 minutes (108 sel/ml) was carried out 15 days after feeding trial. Challenge test was conducted by injection of 0,2 ml bacteria suspension (LD80 concentration) was carried out 15 days after vaccination. Growth rate of the fish was observed monthly. Result of this experiment indicated that mortality in the challenge test due to A. hydrophila infection considerably decreased for treatment combination among vaccination; and 500 and 1000 mg AA/kg feed. These AA levels without vaccination could not reduce mortality.